Unraveling the electronic properties of graphene with substitutional oxygen. (5th October 2021) - Mackenzie, David M A; Galbiati, Miriam; de Cerio, Xabier D; Sahalianov, I Y; Radchenko, Taras M; Sun, Jianbo; Peña, Diego; Gammelgaard, Lene; Jessen, Bjarke S; Thomsen, Joachim D; Bøggild, Peter; Garcia-Lekue, Aran; et al.
Abstract: We show abrupt changes in the electronic properties of graphene with different types of binding to oxygen. Whereas oxygen bonded to the basal plane in the form of functional groups p -type dopes graphene, we prove that substitutional (i.e. in-plane) oxygen n -type dopes it. Moreover, we determine that impurity scattering potentials introduced by these substitutional atoms are notably larger than those of conventional donors, e.g. nitrogen. Both facts ultimately result in a conduction asymmetry in the system with holes being scattered more strongly than electrons. These findings provide essential insights into the impact of oxygen in carbon nanomaterials such as graphene oxide, oxidized carbon nanotubes or novel two-dimensional π -conjugated organic frameworks, promising compounds for a wide range of applications including flexible electronics, catalysis, energy storage or biomedicine.